PERANAN POHON INDUK DAN PENGARUH PEMUPUKAN DAUN TERHADAP POLA PERTUMBUHAN SEMAI CENDANA (Santalum album L.) - Albert H. Wawo; Fauzia Syarif; Budiardjo Budiardjo (The East Java Biological Society, 2008)
Sandalwood (Santalum album L.) is one of the economic plants in Indonesia that is threatened rare, because over exploitation and is not cultivated intensively yet by local people in province of Nusa Tenggara Timur (NTT). Therefore need some obviously activities in conservation. One of those activities is producing sandalwood seedlings for cultivation. Sandalwood seeds were collected from mother seed trees. In recent years was found two mother seed trees that grew in 2 locations in Belu District of NTT province were; Tialai location, subdistrict of Tasifeto Timur and Alas locatian, subdistrict of Kobalima. Sandalwood seeds from two mother seed trees was mentioned have been germinated to produced seedling. One of some activities in maintenance of seedling is fertilizing. In 2006 at Kebun Benih Kian Rai Ikun, Belu have been carried out the study of foliar fertilizing on sandalwood seedling from two mother seed trees was mentioned above Three levels dose of Bayfolan had been sprayed every 2 weeks during 10 weeks. The study used Factorial Completely Randomized Design with 3 replications. The results of this study as follow. The growth of sandalwood seedling was infl uenced by mother seed trees whereas foliar fertilizing with Bayfolan was not give significant effect on growth of sandalwood seedling. Seedling growth from both mother seed trees follow the logistic growth model with determination coeffi cient (R2) = > 0.90.